Energy-Efficient Multi-SPEED Routing Protocol For Wireless Sensor Networks - Babak Namazi; Karim Faez (Institute of Advanced Engineering and Science, 2013)
Wireless Sensor Networks(WSN) consist of a large number of sensor nodes randomly deployed in an area of interest to collect information from the environment. Due to lack of resources, energy efficiency and Quality of Service(QoS) are challenging issues in WSNs. In This paper, a new localized routing protocol is proposed which considers different QoS requirements in WSN. For latency considerations, it takes into account multiple levels of delay requirements by implementing different speed layers. Reliability needs are met by dynamically adjusting the transmission power of the sender and based on the energy consumed at the transmitter and the residual energy of the receiver, the forwarding decision is made. Finally, the performance of the protocol is evaluated using computer simulation.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2294